Pengaruh Koneksi Politik dan Militer pada Pengungkapan Green Banking: Studi pada Perbankan Indonesia - Edi, Edi; Sarwani, Sarwani (Universitas Darwan Ali, 2025)
A company’s reputation plays an important role in shaping how people see the values the company holds. The rising concern about climate change and global warming has made environmentally conscious stakeholders pay more attention to the environmental impact of a company’s activities. This situation has made environmental performance a key factor in helping companies improve their business value. In this context, one strategy that can be used by the banking sector to respond to sustainability issues is adopting a green banking approach. This study aims to examine the influence of political and military connections on green banking disclosure in banking companies listed on the Indonesia Stock Exchange (IDX) during the years 2019–2022. The study uses a quantitative approach. The research population includes 45 banking companies listed on the IDX, and 21 of them met the sample criteria. The findings show that political connections have a significant positive effect on green banking disclosure, while military connections have no significant effect. Companies with political ties tend to be more careful in their operations, which leads them to build a stronger reputation in public, one way being through the disclosure of green banking implementation.